2016
DOI: 10.21037/jtd.2016.12.60
|View full text |Cite
|
Sign up to set email alerts
|

Fibred confocal fluorescence microscopy in the diagnosis of interstitial lung diseases

Abstract: Background: Accurate diagnosis is critical to both therapeutic decisions and prognostication in interstitial lung diseases (ILD). However, surgical lung biopsies carry high complication rates. Fibred confocal fluorescence microscopy (FCFM) offers an alternative as it can visualize lung tissue in vivo at the cellular level with minimal adverse events. We wanted to investigate the diagnostic utility, and safety of using FCFM for patients with ILD.Methods: In patients with suspected ILD, FCFM images were obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 17 publications
4
15
0
3
Order By: Relevance
“…It has previously been shown that elastin is autofluorescent with the CLE wavelength of 488 nm [10] and that an increase and distortion of the elastin fibers is found in the histology of fibrotic lung [14, 15], comparable with our CLE findings. The CLE pattern that we found in densely fibrotic areas resembles the previously described (densely packed fiber) pattern by Meng et al [14], which they hypothesized to be indicative of late-stage scarring.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It has previously been shown that elastin is autofluorescent with the CLE wavelength of 488 nm [10] and that an increase and distortion of the elastin fibers is found in the histology of fibrotic lung [14, 15], comparable with our CLE findings. The CLE pattern that we found in densely fibrotic areas resembles the previously described (densely packed fiber) pattern by Meng et al [14], which they hypothesized to be indicative of late-stage scarring.…”
Section: Discussionsupporting
confidence: 91%
“…The CLE pattern that we found in densely fibrotic areas resembles the previously described (densely packed fiber) pattern by Meng et al [14], which they hypothesized to be indicative of late-stage scarring. Uncertainty remained due to the unavailability of histology specimens of cryobiopsy and surgical biopsy as a reference standard.…”
Section: Discussionsupporting
confidence: 89%
“…The presented method aims to quantify features that have previously been reported to change due to different DPLDs, such as increase/decrease of elastic fibres, disorganization of elastic network and enlarged axial elastic fibre bundle diameter [14][15][16][17]. Similar elastin thickness values were found here as in other work [29], albeit with a higher variability.…”
Section: Plos Onesupporting
confidence: 79%
“…With a multitude of technical improvements over the last 15 years to overcome the low specificity of autofluorescence defects [10,11], pCLE has shown promise as a diagnostic method to visualize lung tissue in vivo [12,13]. Multiple studies [14][15][16][17] have investigated the structural changes of lung tissue caused by different DPLDs and specifically highlighted increased elastin fibre thickness, density of fibres and number of cellular structures as important features. The aim of this study was to develop a fully automatic workflow for quantifying these structural properties using pCLE measurements and to perform a preliminary assessment of their diagnostic potential.…”
Section: Introductionmentioning
confidence: 99%
“…Se han realizado varios estudios para identificar características específicas en imágenes por pECL en EPIs. Meng et al [83] identificaron seis patrones diferentes para discriminar una EPI fibrosante crónica de otras EPIs. Salaün et al [84] identificó nueve características específicas de ECL empleando datos de 80 individuos (59 pacientes con EPI, 21 sujetos sanos).…”
Section: Epis Y Otras Enfermedades Del Parénquima Pulmonarunclassified